Implikasies vir die leksikografie van die klassifikasie van plante en diere in die volkstaksonomie - du Plessis, J.C.M.D. (Lexikos, 1991)
Implications for Lexicography of the Classification of Plants and Animals in Folk Taxonomy In this essay the scientific taxonomic system is contrasted with the folk taxonomic system through the use of relational semantic models: the basis for the former is chiefly meronymy, while that for the latter is mainly modification. Corresponding to these systems two kinds of dictionaries can be distinguished: the encyclopedic dictionary and the standard dictionary which are based on extensional and stereotypical concepts respectively. In a scientifically based culture the scientific taxonomical concepts influence the folk taxonomical concepts of plants and animals. This fact should be taken into account in definitions in a comprehensive explanatory dictionary which is based on prototypical concepts and takes a position between the encyclopedic dictionary and the standard dictionary.